1999
DOI: 10.1002/(sici)1098-1136(199904)26:2<153::aid-glia6>3.0.co;2-z
|View full text |Cite
|
Sign up to set email alerts
|

Mice lacking NT-3, and its receptor TrkC, exhibit profound deficiencies in CNS glial cells

Abstract: Neurotrophin‐3 (NT‐3) and its receptor TrkC are known to be important for neuronal survival. More recently, NT‐3 has been implicated as playing a role in oligodendrocyte (OL) proliferation and survival in vitro. Examination of NT‐3 and TrkC knockout mice revealed a reduction in NT‐3‐dependent neurons. To date, no study has examined alterations in glial cell populations in these knockout mice. In this report, we demonstrate a decline in OL progenitor cell numbers within the CNS of NT‐3 and TrkC knockout mice. W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 89 publications
(43 citation statements)
references
References 56 publications
0
43
0
Order By: Relevance
“…Reductions in both neuronal and glial cell populations have been observed in NT3 knockout mice. 49 Overexpression of trkC inhibits the growth of intracerebral xenografts of a medulloblastoma cell line in nude mice. 44 TrkB knockout mice have decreased densities of axonal varicosities, lower densities of synaptic contacts, and decreased density of synaptic vesicles, 46 a finding that has been suggested in tubers and non-TSC cortical dysplasia.…”
Section: Altered Neurotrophin Expression and Aberrant Cytoarchitecturmentioning
confidence: 99%
See 1 more Smart Citation
“…Reductions in both neuronal and glial cell populations have been observed in NT3 knockout mice. 49 Overexpression of trkC inhibits the growth of intracerebral xenografts of a medulloblastoma cell line in nude mice. 44 TrkB knockout mice have decreased densities of axonal varicosities, lower densities of synaptic contacts, and decreased density of synaptic vesicles, 46 a finding that has been suggested in tubers and non-TSC cortical dysplasia.…”
Section: Altered Neurotrophin Expression and Aberrant Cytoarchitecturmentioning
confidence: 99%
“…For example, BDNF and NT3 promote the morphological differentiation of a subpopulation of GABAergic neurons in cortex 53 and a recent study showed markedly diminished numbers of GABAergic neurons in tubers as evidenced by GAD65 immunolabeling. 37 Similarly, NT3 and trkB have a role in the promotion of activity-dependent inhibitory synaptogenesis 48,49 and thus, reduced NT3 and trkB expression may alter the formation of inhibitory synapses in tubers. Reduced expression of several GABA A receptor subunits has been demonstrated in tubers and thus, a reduction in GABAergic neurons coupled with diminished GABA-mediated receptor inhibition may foster epileptogenesis.…”
Section: Neurotrophin Expression Epilepsy and Epileptogenesismentioning
confidence: 99%
“…In this regard, the TrkB receptor can be activated by BDNF, NT3 and NT4 (also known as Ntf5 -Mouse Genome Informatics) (Huang and Reichardt, 2003), and whereas previous work (Jones et al, 1994;Alcantara et al, 1997;Ringstedt et al, 1998;Xu et al, 2000;Lotto et al, 2001;Medina et al, 2004) has indicated that BDNF-mediated TrkB activation is important for cortical development in vivo, these studies concluded that any observed perturbations were a consequence of altered TrkB signaling in cortical neurons. The TrkC receptor is only activated by NT3, and previous work on Nt3 -/-and TrkC -/-mice has primarily focused upon the profound deficits observed in the peripheral nervous system (Ernfors et al, 1994;Wilkinson et al, 1996;Klein et al, 1994;Tessarollo et al, 1994), or on perturbations in the biology of committed CNS glia or neurons (Minichiello and Klein, 1996;Martinez et al, 1998;Kahn et al, 1999;Ma et al, 2002;von Bohlen und Halbach et al, 2003). As both BDNF and NT3 are known to be expressed in precursor cells of the cortical neuroepithelium (Maisonpierre et al, 1990;Fukumitsu et al, 1998;Behar et al, 1997;Barnabé-Heider and Miller, 2003;Fukumitsu et al, 2006), and as cortical precursors express both of these receptors (Tessarollo et al, 1993;Behar et al, 1997;Barnabé-Heider and Miller, 2003), we have chosen to disrupt signaling via these two receptors both individually and together.…”
Section: Introductionmentioning
confidence: 99%
“…Recent evidence indicates roles for neurotrophin-3 and colony stimulating factor-1 (CSF-1), which are expressed in the developing brain. (Michaelson et al, 1996;Calvo et al, 1998;Wegiel et al, 1998;Kahn et al, 1999).…”
mentioning
confidence: 99%